The effect of the multiple genotypes of Myostatin gene on reproductive characteristics of the Iraqi brown local chickens - Hanan Kareem Noor Al-Musawi; Majid Mohsen Salman Al-Ameri (Kufa Journal for Agricultural Sciences)
The experimental flock consisted of 101 laying hens attributed to the Sire and Dam from the local Iraqi chickens at the age of 74 weeks / the third generation belonging to the fields of the Poultry Research Station in the Agricultural Research Department / Ministry of Agriculture. Hens were selected based on the characteristic of high egg production rate which was more than 60%, the study aims to determine the multiple genetic features of the Myostatin gene (MSTIN) and its contribution to affecting the average body weight in a sample of Iraqi brown local chickens.blood samples were collected and DNAextracted DNA with a concentration of 98% and a purity of 19.8, PCR-Product technique was used to multiply the segment of the Myostatin gene, and sent to the Republic of South Korea, Macrogen Corporation-Korea, and using the Sanger and Coulson method, the genotypes of genetic mutations were,by sequencing the percentages of individuals carrying it contributed to the variance of genetic frequency and chi-square values (24.8, 58.5 and 37.6 for mutations, respectively) and their incompatibility with the Hardy-Weinberg rule. The hybrid genotypes (CG, AB, and TC) showed significant p<0.05 in the weekly egg production rate throughout the productive periods,While there were no significant differences in the average weight of the first egg (36.32, 36.37 and 36.32 g for mutations, respectively), as well as no significant difference in the measures of egg quality (white and yolk weight and their percentages) among all individual of the local brown chicken under study.